Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1080/0020739x.2021.1941361
|View full text |Cite
|
Sign up to set email alerts
|

Education for sustainable development in mathematics education: what could it look like?

Abstract: Over the past two decades, there has been a loud call around us to integrate Education for Sustainable Development (ESD) across all subjects in the primary and secondary curricula. However, researchers have argued that sustainability and mathematics education remain largely unconnected in actual classrooms. The question as to what sustainable mathematics education could look like in the 21st century remains unanswered. There is a pressing need to rethink, re-envision mathematics teaching and learning for 21st-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 31 publications
0
26
0
1
Order By: Relevance
“…Recently it has been suggested that sustainability and mathematics education remain largely disconnected from the reality of the classroom [31]. A change in pedagogical model is needed to address sustainability in the area of mathematics; in this sense, active pedagogies represent promising means to achieve this goal.…”
Section: Sustainability and Mathsmentioning
confidence: 99%
“…Recently it has been suggested that sustainability and mathematics education remain largely disconnected from the reality of the classroom [31]. A change in pedagogical model is needed to address sustainability in the area of mathematics; in this sense, active pedagogies represent promising means to achieve this goal.…”
Section: Sustainability and Mathsmentioning
confidence: 99%
“…With an exception of Summer's (2020) exploration of how a sustainable primary mathematics education ought to be implemented [33], other works that intersect between sustainability and mathematics education usually concentrate around ESD instead of SLE, e.g., [34][35][36][37][38][39]. By suggesting concrete pedagogical initiatives to tackle primary students' challenges in learning mathematics, Summer (2020) demonstrated that quality education and competent teachers not only decrease their learning difficulties but also equip children with essential mathematical and critical thinking skills [33].…”
Section: Sustainable Learning In Mathematics Educationmentioning
confidence: 99%
“…According to [2], ESD implementation demands several things, including redesigning policies, curricula, pedagogy, and educational training. Adapting and integrating ESD into education systems is seen as one aspect of boosting quality education, and whole institution approaches (WIA) to sustainability are recommended by various studies [1,3,7,12]. However, "the consistent transfer of ESD into learning environments through whole system approaches within specific educational organizations remains a considerable challenge" [2].…”
Section: Introductionmentioning
confidence: 99%